HUBUNGAN BUDAYA ORGANISASI DENGAN QUALITY OF NURSING WORKLIFE PADA PERAWAT RAWAT INAP DI RSUD X JAKARTA - Siregar, Tatiana; Afriyani, Yana (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
The quality of nurses' work life is very important for the sustainability of a hospital management because with a high quality of nurses' work life, there will also be low job dissatisfaction with organizational culture and nurses' desire to leave the workplace. The purpose of the study was to determine the relationship between organizational culture and quality of nursing worklife in inpatient nurses at RSUD X Jakarta. Quantitative research design with a CrossSectional approach. The research sample used purposive sampling with a total sample of 128 nurses in the inpatient room of RSUD X Jakarta. Data analysis using Chi Square statistical test with CI 95% results p-value 0.001 which means <0.05 so it is concluded that there is a significant relationship between organizational culture and the quality of nursing work life for inpatient nurses at RSUD X Jakarta. For hospital management to maintain the dimension of team orientation so that it will improve the quality of nursing work life in nurses, for nurses to pay attention to the 7 (seven) dimensions of organizational culture, especially for the dimensions of innovation and risk-taking, and educational institutions are expected to be a reference and increase knowledge, especially nursing regarding organizational culture with quality of nursing worklife so that it can be used as learning.